Hobbes : A Guide for the Perplexed - Finn, Stephen J. (London Continuum, 2007)
Thomas Hobbes is one of the foremost British philosophers. This title covers those areas of philosophy where Hobbes is a key player: metaphysics; epistemology; moral philosophy; political philosophy; the philosophy of religion. It explores Hobbes' philosophical method, and offers an account of the historical background to Hobbes' thought.
Include Notes, Bibliography and Index
Keywords: Hobbes, Thomas, 1588-1679